2020
DOI: 10.1088/1475-7516/2020/10/034
|View full text |Cite
|
Sign up to set email alerts
|

A Lagrangian perturbation theory in the presence of massive neutrinos

Abstract: We develop a Lagrangian Perturbation Theory (LPT) framework to study the clustering of cold dark matter (CDM) in cosmologies with massive neutrinos. We follow the trajectories of CDM particles with Lagrangian displacements fields up to third order in perturbation theory. Once the neutrinos become non-relativistic, their density fluctuations are modeled as being proportional to the CDM density fluctuations, with a scale-dependent proportionality factor. This yields a gravitational back-reaction that introduces … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 72 publications
3
83
0
Order By: Relevance
“…This increased precision, however, comes at the cost of very large inaccuracies beyond the nonlinear scale at which the self-gravitating dark matter fluid ceases to be perturbative (Blas et al 2014;McQuinn & White 2016). In addition, perturbative frameworks provide a rigorous, first-principles approach to include physics beyond the standard ΛCDM model in large-scale structure observables such as neutrinos, baryonic effects and more exotic early-universe scenarios (Lewandowski et al 2015;Senatore & Zaldarriaga 2017;Aviles & Banerjee 2020;Chen et al 2020c;Laguë et al 2020;Ivanov et al 2020; ? ; .…”
Section: Introductionmentioning
confidence: 99%
“…This increased precision, however, comes at the cost of very large inaccuracies beyond the nonlinear scale at which the self-gravitating dark matter fluid ceases to be perturbative (Blas et al 2014;McQuinn & White 2016). In addition, perturbative frameworks provide a rigorous, first-principles approach to include physics beyond the standard ΛCDM model in large-scale structure observables such as neutrinos, baryonic effects and more exotic early-universe scenarios (Lewandowski et al 2015;Senatore & Zaldarriaga 2017;Aviles & Banerjee 2020;Chen et al 2020c;Laguë et al 2020;Ivanov et al 2020; ? ; .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the mean matter pairwise velocity decreases with increasing neutrino mass at those pair separations. For analytical predictions, Aviles & Banerjee (2020) studied the effect of massive neutrinos on pairwise velocity using Lagrangian perturbation theory for biased tracers at quasi-linear scales and above. The pairwise velocity measurement from kSZ experiments has been shown to be a novel probe to constrain the summed neutrino mass (Mueller et al 2015b), and provide complementary constraints with respect to galaxy clustering and CMB experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The neutrino flavour oscillations provide strong evidence of non null masses for these particles, this fact is also considered as one of the proofs for physics beyond the standard model of particles. However, despite their very small masses they have a non negligible contribution to the total cosmological density at low redshifts playing a relevant role on the formation of large scale structures [39]. The avoidance of clustering of matter inhomogeneities could also be due to the neutrino presence.…”
Section: B Massive Neutrinosmentioning
confidence: 99%